Black girl magic: strength, resiliency, and suffering? A qualitative exploration of toxic black femininity and intimate partner violence - Kelly, Lorin Camille (Kansas State University, 2021)
This phenomenological study explored the experiences of Black women who survived Intimate Partner Violence (IPV) and their experiences with Toxic Black Femininity (TBF). This study used the TBF, Post-Traumatic Slave Syndrome, and Intersectionality to highlight and explore the lived experiences of Black women and TBF, systemic racism, and help-seeking behaviors in regard to IPV victimization. Research was conducted with 6 participants who identified as Black, female, and survivor. Four themes emerged from the data: 1) Intersectionality directly impacted participant’s experience of IPV, TBF, and help-seeking, 2) Self-blame and rationalization was used as a protective mechanism against IPV and TBF, 3) Help-seeking was directly impacted by intersectionality and TBF, and 4) most of the participants in this study self-reported as queer yet only reported on male perpetration, thus highlighting the interaction between TBF and sexually diverse identities. These findings highlight the intergenerational transmission of survival skills and narratives that have been passed down to Black women since the time of slavery and how systemic racism and TBF keep these narratives in play.
Keywords: Intimate partner violence; Black women; Toxic black femininity; Post-traumatic slave syndrome; Help-seeking behaviors